EVALUATION OF NATIONAL FADAMA II PROJECT IN KAFUR LOCAL GOVERNMENT AREA OF KATSINA STATE: IMPLICATION FOR EXTENSION EDUCATION - SULEIMAN, SANUSI (Sokoto Educational Review, 2025)
This study evaluated the impact of the National Fadama II project in Kafur Local Government Area, Katsina State. Employing a descriptive survey design, the research utilized stratified random sampling to select 297 beneficiaries from a population of 1,300. Additionally, purposive sampling was used to select 6 extension agents and 3 Fadama officials. Data were collected using the "Fadama II Beneficiaries Impact Assessment Questionnaire (FIIBIAQ)." The findings revealed that the Fadama II Project significantly improved agricultural productivity, rural infrastructure, and poverty reduction in the area. Notably, project beneficiaries and extension agents actively participated in both the planning and implementation phases. Extension agents played a crucial role in disseminating valuable knowledge to the beneficiaries. The study recommends the timely distribution of seeds and fertilizer to further enhance farm productivity, as well as increased support from governmental and non-governmental organizations to strengthen poverty reduction efforts. DOI: https://doie.org/10.0304/SER.2025805442